Reflections on the economics of socialism - Nick Rogers (Journal of Global Faultlines, 2023)
Socialist economic management should be reconceptualized. Economic planning conceived as the ex ante allocation of everything that is to be produced in any given production cycle does not capture how any organization, let alone a whole economy, works. Planning should involve preparing in advance to respond flexibly to a range of possible eventualities. The way corporations, such as Walmart and Amazon, manage their supply chains points towards how non-commodity production and non-market allocation could work efficiently, while responding flexibly to the consumers of a socialist economy. Openness, sharing of information, and transparency about the use of labor-time in the economy (we should take Marx’s discussion of “labour certificates” seriously) are critical to overcoming the fragmentation of decision-making that is a key feature and a key weakness of a capitalist economy. A system of socialist goal-directed economic coordination could outperform capitalism in the provision of goods and services, while enabling economic decision-making to be decentralized and political power dispersed throughout society, so as to make a reality of the “withering away of the state”.